The Correlation between the Energy Gap and the Pseudogap Temperature in Cuprates: The YCBCZO and LSHCO Case - R. Szczȩśniak; M. W. Jarosik; A. M. Duda (Advances in Condensed Matter Physics)
The paper analyzes the influence of the hole density, the out-of-plane or in-plane disorder, and the isotopic oxygen mass on the zero temperature energy gap (2Δ(0)) Y1-xCaxBa2Cu1-yZny3O7-δ (YCBCZO) and La1.96-xSrxHo0.04CuO4 (LSHCO) superconductors. It has been found that the energy gap is visibly correlated with the value of the pseudogap temperature (T⋆). On the other hand, no correlation between 2Δ(0) and the critical temperature (TC) has been found. The above results mean that the value of the dimensionless ratio 2Δ0/kBTC can vary very strongly together with the chemical composition, while the parameter 2Δ(0)/kBT⋆ does not change significantly. In the paper, the analytical formula which binds the zero temperature energy gap and the pseudogap temperature has been also presented.